Peningkatan Keamanan Sistem Informasi Berbasis Laravel 12 dengan Rate Limiting dan Role-Based Access Control (RBAC) - Mary, Thomson; Febriyani, Nia (Prodi Sistem Informasi Universitas Dharma Andalas, 2025)
This study aims to enhance the security of a Laravel 12-based news information system by implementing Rate Limiting and Role-Based Access Control (RBAC). The current website-based information system is vulnerable to hacking and redirection to online gambling sites, indicating serious security weaknesses in the programming. Leveraging the robust capabilities of Laravel 12, this research implements security features such as rate limiting to prevent brute force attacks and RBAC to manage user access rights based on roles. In addition, it utilizes the advanced security features of Spatie Role Permissions in Laravel 12 to achieve layered protection. This is supported by the use of the MariaDB database in conjunction with Laravel 's Spatie Permissions package for more structured permission management. The research method employed is evaluative with a quantitative and descriptive approach, used to measure and analyze the quality of the software code before and after improvements. The results of this study provide a more secure solution for the information system.